Legal Protection of Indonesian Migrant Workers Affected by Covid-19 - Nur Putri Hidayah; Komariah Komariah; Fitria Esfandiari; Abdul Kadir Jaelani (Jurnal Cita Hukum, 2022)
Covid-19 has interrupted the fulfillment of Indonesian migrant workers’ rights, while the State has promulgated Law Number 11 of 2020 concerning Job Creation and revised Law Number 18/2017 concerning Protection of Indonesian Migrant Workers. This research aims to find out how protection and law reinforcement are given to Indonesian migrant workers by the state during the pandemic according to Law Number 18/2017 in conjunction with Law Number 11/2020. This research employed a normative method and a statutory approach. The research results have revealed that according to Law Number 18/2017, the protection given to the migrants only took repatriation, and another form of protection is still deemed to be not optimal since it did not take the engagement of roles of the companies sending Indonesian migrants. Moreover, pursuant to Law Number 11/2020, there is no reinforcement implied since the changes taking place are likely to ease administrative measures, contrary to the fact that strict permits could reduce the likelihood of illegal and non-procedural placement of migrant workers. This issue affects the fulfillment of the rights of Indonesian migrant workers, especially during the pandemic. Thus, it is essential that the state reinforce the protection given to Indonesian migrant workers during the pandemic by reinforcing legal protection every company providing labor placement service has to take into account and by imposing administrative measures as sanctions or sentencing in case of failing to abide by regulations. Moreover, permit issuance to the companies running labor placement services for Indonesian migrants has to be made stricter to ensure that only credible companies pass the requirement of migrant placement services, allowing the status of the rights of Indonesian migrant workers to be properly met amidst the pandemic. Keywords: legal protection; Indonesian migrant workers; COVID-19 Perlindungan Hukum Buruh Migran Indonesia yang Terdampak Covid-19AbstrakCovid-19 telah mengganggu pemenuhan hak-hak pekerja migran Indonesia, sedangkan negara telah menerbitkan Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja dan merevisi Undang-Undang Nomor 18 Tahun 2017 tentang Perlindungan Tenaga Kerja Indonesia. Penelitian ini bertujuan untuk mengetahui bagaimana perlindungan dan penguatan hukum yang diberikan negara kepada pekerja migran Indonesia di masa pandemi menurut Undang-Undang Nomor 18/2017 jo Undang-Undang Nomor 11/2020. Penelitian ini menggunakan metode normatif dan pendekatan perundang-undangan. Hasil penelitian mengungkapkan bahwa menurut Undang-Undang Nomor 18 Tahun 2017 perlindungan yang diberikan kepada TKI hanya berupa pemulangan, dan bentuk perlindungan lainnya masih dirasa belum optimal karena tidak melibatkan peran perusahaan pengirim TKI. Apalagi, menurut Undang-Undang Nomor 11/2020, tidak ada penguatan yang tersirat karena perubahan yang terjadi cenderung memudahkan tindakan administratif, padahal izin yang ketat dapat mengurangi kemungkinan penempatan pekerja migran ilegal dan non-prosedural. Isu ini berdampak pada pemenuhan hak-hak pekerja migran Indonesia, terutama di masa pandemi. Oleh karena itu, negara perlu memperkuat perlindungan kepada TKI di masa pandemi dengan memperkuat perlindungan hukum yang harus diperhatikan oleh setiap perusahaan penyedia jasa penempatan tenaga kerja dan dengan memberikan tindakan administratif berupa sanksi atau hukuman jika tidak mematuhi peraturan.Kata Kunci: Perlindungan Hukum; Pekerja Migran Indonesia; COVID-19. Правовая Защита Индонезийских Трудовых Мигрантов, Пострадавших от Covid-19 АннотацияCovid-19 помешал осуществлению прав индонезийских трудовых мигрантов, в то время как государство обнародовало Закон № 11 от 2020 г. о создании рабочих мест и пересмотрело Закон № 18/2017 о защите индонезийских трудовых мигрантов. Цель этого исследования - выяснить, каким образом государство обеспечивает защиту и укрепление законодательства индонезийским трудовым мигрантам во время пандемии в соответствии с Законом № 18/2017 в сочетании с Законом № 11/2020. В этом исследовании использовался нормативный метод и законодательный подход. Результаты исследования показали, что в соответствии с Законом № 18 от 2017 г. защита, предоставляемая TKI (Индонезийским трудовым мигрантам), предусматривает только репатриацию, а другая форма защиты по-прежнему считается неоптимальной, поскольку она не предполагает участия компаний, отправляющих индонезийских трудовых мигрантов. Более того, в соответствии с Законом № 11/2020 не подразумевается никакого усиления, поскольку происходящие изменения, вероятно, облегчат административные меры, вопреки тому факту, что строгие разрешения могут снизить вероятность незаконного и непроцессуального размещения трудовых мигрантов. Эта проблема влияет на соблюдение прав индонезийских трудовых мигрантов, особенно во время пандемии. Таким образом, важно, чтобы государство усилило защиту, предоставляемую индонезийским трудовым мигрантам во время пандемии, усилив правовую защиту, которую должна учитывать каждая компания, предоставляющая услуги по трудоустройству, и путем введения административных мер в виде санкций или наказания в случае несоблюдения правил. Кроме того, необходимо ужесточить выдачу разрешений компаниям, предоставляющим услуги по трудоустройству индонезийских трудовых мигрантов, чтобы гарантировать, что только заслуживающие доверия компании удовлетворяют требованиям служб трудоустройства трудовых мигрантов, что позволит должным образом соблюдать статус прав TKI в условиях пандемии.Ключевые слова: Правовая защита; Индонезийские трудовые мигранты; COVID-19.